If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3ax + y) = 5ax + -5y (3ax * 2 + y * 2) = 5ax + -5y (6ax + 2y) = 5ax + -5y Solving 6ax + 2y = 5ax + -5y Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5ax' to each side of the equation. 6ax + -5ax + 2y = 5ax + -5ax + -5y Combine like terms: 6ax + -5ax = 1ax 1ax + 2y = 5ax + -5ax + -5y Combine like terms: 5ax + -5ax = 0 1ax + 2y = 0 + -5y 1ax + 2y = -5y Add '-2y' to each side of the equation. 1ax + 2y + -2y = -5y + -2y Combine like terms: 2y + -2y = 0 1ax + 0 = -5y + -2y 1ax = -5y + -2y Combine like terms: -5y + -2y = -7y 1ax = -7y Divide each side by '1x'. a = -7x-1y Simplifying a = -7x-1y
| S/1.4=12 | | N-5*10=20 | | x^3-7x^2-8x-12=0 | | N-10*2=16 | | 2(2x+3)/5 | | y/23=-2.5 | | 0.02(y-4)+0.16y=0.20y-0.01(20) | | 7x+3=19-x | | 341=d | | b-1+3b=24 | | 5c(c-2)=6+3c | | -4.3k=21.5 | | y=-2-3x | | 3s^2-24= | | 1/5x^2-8/5x+1/5=0 | | 34x=244.8 | | -5x+7=-27 | | w/-6=4.2 | | 1.5c=20-2 | | w/7=-9 | | B^2-4b+3=0 | | r/9=5.4 | | 23t=460 | | -8=-3x+7 | | (12x+3)-(5x-2)=19 | | 24x^2=14+50x | | 14x=21 | | -3.2c=-9.6 | | 24/6 | | x^2+12x-35= | | 5x+5/6+4x+5/2=9 | | -2x+4y=7 |